Perceived Family Functionality among Elderly Patient with Covid-19 Infection: A Perspective from Developing Country - Sri Sunarti; Didi Candradikusuma; Dewi Indiastari; Siti Fatma Prehatiningsih; Bogi Pratomo Wibowo; Affa Kiysa Waafi (Jurnal Kedokteran Brawijaya, 2022)
Family is a basic social unit of senior citizen. Relationship among family members considered as source of emotional comfort. Meanwhile, economic, political, and social changes during pandemic has an impact on the family, the support provided can be manifested among vulnerable groups such as the elderly. Prolonged stress due to isolation care of Covid-19 infection increase psychological distress by reducing family support. This study aimed to explore perceived family function among elderly patients after Covid-19 infection. A cross sectional study was conducted among 33 elder patients with history of Covid-19 infection in Saiful Anwar General Hospital, Indonesia. Perceived family functionality was evaluated using APGAR family score. Data was analyzed using descriptive analyses, independent T test, correlation and regression. Mean total APGAR score was 9.610.70 with joint pain had significant association with APGAR score (p 0.021) indicating full family support in elder person with symptoms. Gender female was associated with 'Resolve' (p 0.038) which might correlate with bigger role of elder female in Indonesian family. Length of stay was significantly associated with 'Partnership' (p 0.012) and 'Growth' (0.043) with inverse correlation. It showed how prolonged hospital stay affected family relationship especially in terms of communication. Perceived family supports remained high in elderly during Covid-19 isolation in Indonesia. Specific symptoms such as joint pain, even strengthen the family support for elder member of family. Prolonged stay in the hospital during Covid-19 infection, might become a communication barrier between elder person and the family which affect decision sharing and emotional expression.